A Divalent Pentastable Redox‐Switchable Donor–Acceptor Rotaxane. Issue 12 (1st February 2017) - Schröder, Hendrik V.; Hupatz, Henrik; Achazi, Andreas J.; Sobottka, Sebastian; Sarkar, Biprajit; Paulus, Beate; Schalley, Christoph A.
Abstract: Donor–acceptor materials with small HOMO–LUMO gaps are important in molecular electronics, but are often difficult to synthesise. A simple and efficient way to position tetrathiafulvalene (TTF) as the donor and naphthalene diamide (NDI) as the acceptor in close proximity to each other in a divalent crown/ammonium pseudo[2]rotaxane is presented. The divalent design provides high chelate cooperativity and much stronger binding compared with a monovalent analogue. The pseudo[2]rotaxane was then doubly interlocked by stoppering it in a catalyst‐free 1, 3‐dipolar cycloaddition. UV/Vis and cyclic voltammetry experiments with the resulting [2]rotaxane revealed the optoelectronic properties of an intramolecular charge transfer with a small HOMO–LUMO energy gap. Redox‐switching experiments showed the rotaxane to be pentastable. DFT calculations provided insights into the electronic structures of the five redox states. Abstract : Click the brick : Donor–acceptor materials are important for molecular electronics. A straightforward multivalent self‐assembly approach is presented, in which donor and acceptor units are "clicked" together like building bricks to force their spatial proximity (see figure). Emergent optoelectronic properties and electrochemical switching were investigated and are supported by theoretical calculations.